A social distancing measure governing the whole proteome. (February 2021) - Choi, Seong Il; Seong, Baik L
Abstract : Protein folding in vivo has been largely understood in the context of molecular chaperones preventing aggregation of nascent polypeptides in the crowded cellular environment. Nascent chains utilize the crowded environment in favor of productive folding by direct physical connection with cellular macromolecules. The intermolecular repulsive forces by large excluded volume and surface charges of interacting cellular macromolecules, exerting 'social distancing' measure among folding intermediates, could play an important role in stabilizing their physically connected polypeptides against aggregation regardless of the physical connection types. The generic intrinsic chaperone activity of cellular macromolecules likely provides a robust cellular environment for the productive protein folding and solubility maintenance at the whole proteome level.